Digital Trash Value: Marketing of Waste Treatment Innovation Products to MSMEs - Wuryandari, Nur Endah Retno; Damayanti, Ida Royani; Purwanto, Setiyo (Teumulong: Journal of Community Service, 2024)
This Community Service Program aims to empower MSMEs through marketing strategies from the innovative processing of banana peel and catfish head waste into products with high economic value. The approach used involves the integration of waste treatment technology with a sustainability-based digital marketing strategy. This program is designed to answer the problem of organic waste from vegetable residues including banana peels and catfish heads, which has been adding to the waste problem. On the other hand, the challenge of Kemuning MSMEs in accessing a wider market through digital technology. The outputs of this program include increasing the capacity of MSME partners in waste treatment, creating competitive environmentally friendly products, and increasing market access through digital media. The program's excellence lies in the integration of a holistic and innovative approach, which focuses not only on waste treatment, but also on marketing aspects to create added value for products in a sustainable manner. The results of this program are expected to encourage local economic growth, reduce the environmental impact of organic waste, and increase public awareness of the importance of more responsible waste management. Thus, this program makes a real contribution to the development of innovation-based and sustainability-based MSMEs.